Commius - An email based interoperability solution tailored for SMEs - Burkhart, T.; Werth, D.; Loos, P. (Journal of Digital Information Management, 2008)
More than 99% of European enterprises are SMEs (Small and Medium-sized Enterprises). While in the current market situation collaboration is evolving to an indispensable key factor of success, research is yet to produce results which can be used by SMEs. This paper introduces an interoperability approach in the context of the European Commius Project which enables SMEs collaborate easily on the level of process interoperability. The Commius solution will dock onto existing E-Mail structures and enrich incoming E-Mails with additional information dependant upon its content and provide recommendations of expedient further steps to process the E-Mail. A first picture of the Commius process interoperability layer architecture will be drawn. Furthermore proposals to adapt Commius to the specific processes every SME has, in a simple way, are being exposed.
Keywords: Business process; Collaboration; Email; Interoperability; SME